Which HR Bundles are Utilized in Social Enterprises? The Case of Social Enterprises in Thailand. Issue 2 (4th May 2018) - Napathorn, Chaturong
ABSTRACT: This paper bridges the literatures on social enterprises and human resource management to examine the human resource (HR) bundles utilized by social enterprises and how these HR bundles are different from those used by the typical business enterprises described in the literature. It applies a cross-case analysis of five social enterprises across industries in Thailand. The case study evidence in this paper draws on semi-structured interviews with each social enterprise's founders or managers and employees, field visits to each social enterprise and a review of archival documents and web-based reports and resources. Based on these five case studies, this paper proposes that the HR bundles utilized by social enterprises consist of the following: recruitment and selection via sub-stream or alternative recruitment channels, paying more attention to on-the-job training than to classroom training, focusing more on intrinsic rewards than on extrinsic rewards and paternalistic styles of employee relations with no labour unions. These HR bundles are different from those used by typical business enterprises in that the latter group of enterprises primarily focuses on recruitment and selection via mainstream recruitment channels, training via classroom training and several other types of employee development methods including on-the-job training, both external and intrinsic rewards, and systematic conflict resolution process. It, however, is possible that both typical business enterprises and social enterprises can achieve the same objective of becoming high-performance organizations based on different types of HR bundles. That said, the concept of 'equifinality' is applicable in both typical business enterprises and social enterprises.